THE EFFECT OF CONTENT REVIEW AND PROMOTION ON BUYING INTEREST WITH PRODUCT INVOLVEMENT AS AN INTERVENING : (Case Studies Of Tasya Farasya's Beauty Vlogger Review On Wardah Products) - Sonia Risyafani; Johannes Johannes; Idham Khalik (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
This research aims to explain the influence of product review content and promotions through social media on buying interest through product involvement. Sampling size was determined with the quote technique; 115 respondents were chosen from management students, Faculty of Economics and Business, University of Jambi. The data analysis used PLS (Partial Least Square). The results showed that product review content has a positive and significant effect on buying interest, and promotion positively and significantly impacts buying interest. Product review content has a significant positive effect through product involvement as an intervening variable, and promotion through social media has a positive and significant impact on buying interest through product involvement. Based on the study results, the marketer can suggest social media as a product promotion tool because social media can reach market segments effectively and efficiently and encourage marketers to work with beauty vloggers who have the credibility to attract consumer buying interest.